Evaluating Islamic Bank Efficiency and Productivity in ASEAN: Does Technological Advancement Play a Role? - Riani, Ririn; Ikhwan, Ihsanul; Rusydiana, Aam Slamet (AL-MUZARA'AH, 2024)
Amid the economic crises triggered by the COVID-19 pandemic, sustainable financial systems have become essential for resilience and recovery, particularly in ASEAN countries where Islamic banks play a crucial role in economic stability. The purpose of this study is to evaluate the performances of the Islamic Bank in the ASEAN countries in terms of both efficiency and productivity. This study provides insights into 33 Islamic banks in Indonesia, Malaysia, Brunei Darussalam, Thailand, and the Philippines from 2015 to 2022. This study employs the Data Envelopment Analysis (DEA) technique and the Malmquist Productivity Index (MPI) to simultaneously attain elevated levels of efficiency and productivity. The result shows that Maybank Islamic Berhad was considered the most efficient and productive Islamic Bank within ASEAN countries. In terms of significant elements, it was discovered that shifts in technology capabilities have a greater magnitude of effect on Islamic banking productivity in ASEAN than shifts in innovation strategies and operational efficiencies. The findings also show that Islamic banks in ASEAN region experienced a growth in banking performance during the research period. This implies that the Islamic banking sector demonstrated enhanced performance despite the adverse effects of the COVID-19 pandemic. This study suggests that all ASEAN Islamic banks must continue to enhance the quality of their technology in order to raise their efficiency and generate more productivity in the future.